Killing Two Cells with One Stone: Pharmacologic BCL-2 Family Targeting for Cancer Cell Death and Immune Modulation - Ludwig, Lindsey M.; Nassin, Michele L.; Hadji, Abbas; LaBelle, James L. (Frontiers in Pediatrics, 2016)
A crucial component of regulating organismal homeostasis is maintaining proper cell number and eliminating damaged or potentially malignant cells. Apoptosis, or programmed cell death, is the mechanism responsible for this equilibrium. The intrinsic apoptotic pathway is also especially important in the development and maintenance of the immune system. Apoptosis is essential for proper positive and negative selection during B- and T-cell development and for efficient contraction of expanded lymphocytes following an immune response. Tight regulation of the apoptotic pathway is critical, as excessive cell death can lead to immunodeficiency while apoptotic resistance can lead to aberrant lymphoproliferation and autoimmune disease. Dysregulation of cell death is implicated in a wide range of hematological malignancies, and targeting various components of the apoptotic machinery in these cases is an attractive chemotherapeutic strategy. A wide array of compounds has been developed with the purpose of reactivating the intrinsic apoptotic pathway. These compounds, termed BH3 mimetics are garnering considerable attention as they gain greater clinical oncologic significance. As their use expands it will be imperative to understand the effects these compounds have on immune homeostasis. Uncovering their potential immunomodulatory activity may allow for administration of BH3 mimetics for direct tumor cell killing as well as novel therapies for a wide range of immune-based directives. This review will summarize the major proteins involved in the intrinsic apoptotic pathway and define their roles in normal immune development and disease. Clinical and pre-clinical BH3 mimetics are described within the context of what is currently known about their ability to affect immune function. Prospects for future anti-tumor immune amplification and immune modulation are then proposed.